Utilisation of Sentinel-1 SAR Imagery for Oil Spill Mapping: A Case Study of Balikpapan Bay Oil Spill - Ratna Prastyani; Abdul Basith (Jurnal Geospasial Indonesia, 2018)
Oil spill is a great threat for marine ecosystem. Oil discharge has become a public concern in all over the world with the increase of marine traffics. Indonesian government has declared state of emergency over oil spill which devastated Balikpapan bay in March 2018. The deadly oil spill impacts marine ecosystem as well as the communities. This study aims to map the oil spill over Balikpapan bay by utilising SAR imagery of Sentinel-1. Automatic and semi-automatic approaches are presented in this study to detect the oil spill. Oil spill is automatically detected using Oil Spill Detection toolbox of Sentinel Application Platform (SNAP). Furthermore, semi-automatic method is also demonstrated by utilising pre and post-oil spill SAR imageries. Our experiment shows that semi-automatic method has better performance than automatic detection by SNAP. Nevertheless, both approaches are useful to map oil spill in term of time and cost effectiveness.